Pendekatan Pembelajaran STEM untuk menghadapi Revolusi Industry 4.0 - Tri Mulyani (Pascasarjana Universitas Negeri Semarang, 2019)
Abstract. STEM (Science, Technology, Engineering, and Mathematics). Facing the industrial revolution4.0 requires education with an approach that can equip students with competencies that are inaccordance with the era. With the STEAM approach, individuals can compete globally to face morecomplex changes or progress. Learning with the STEM approach is actually able to train students to beable to communicate, collaborate, think critically and solve problems, as well as creativity andinnovation so that students will be able to face global challenges. In this paper, we report the study ofliterature studies by finding theoretical references relevant to the case or problem found. This review isbased on empirical and conceptual journals about STEM